Synthesis, Molecular Docking, and ADMET Study of N1-Hydrogen and N1-Benzoyl Pyrazoline as Antibacterial Agents - Tjitda, Putra Jiwamurwa Pama; Jumina, Jumina; Wahyuningsih, Tutik Dwi (Chiang Mai University Journal of Natural Sciences, 2022)
Syntheses of N1-hydrogen and N1-benzoyl pyrazoline derivatives and their antibacterial in vitro and in silico assays have been carried out. N1-Hydrogen pyrazoline derivatives were synthesized by cyclization of 2’-hydroxy chalcone, and the subsequent substitution reaction produced N1-benzoyl pyrazoline derivatives. The in vitro antibacterial assay was carried out by disc diffusion method. In silico evaluation was performed via molecular docking against ecKAS III enzyme (ID PDB: 1hnj) and ADMET prediction was carried out using pkCSM tool. The synthesis results showed that N1-hydrogen and N1-benzoyl pyrazoline derivatives were yielded in 50-83%. Antibacterial test results indicated that the presence of N1-benzoyl substituent decreased the antibacterial activity and was only active on Gram-positive bacteria. In comparison, the N1-hydrogen pyrazolines exhibited good antibacterial activity against both Gram-positive and negative bacteria. The ADMET result confirms that compound 2 has the potential to be evolved as a drug in the future.